Multicentre study of the learning curve and surgical performance of cytoreductive surgery with intraperitoneal chemotherapy for pseudomyxoma peritonei. Issue 13 (20th October 2014) - Kusamura, S; Moran, B J; Sugarbaker, P H; Levine, E A; Elias, D; Baratti, D; Morris, D L; Sardi, A; Glehen, O; Deraco, M; Gilly, F N; Barrios, P; et al.
Abstract: Background: The learning curves for cytoreductive surgery with intraperitoneal chemotherapy for treatment of pseudomyxoma peritonei (PMP) were explored between international centres/surgeons to identify institutional or other factors that might affect performance. Methods: Data from patients with PMP treated with the combined procedure across 33 international centres between 1993 and 2012 were analysed retrospectively. A risk-adjusted sequential probability ratio test was conducted after defining the target outcome as early oncological failure (disease progression within 2 years of treatment), an acceptable risk for the target outcome (odds ratio) of 2, and type I/II error rates of 5 per cent. The risk prediction model was elaborated and patients were evaluated sequentially for each centre/surgeon. The learning curve was considered to be overcome and proficiency achieved when the odds ratio for early oncological failure became smaller than 2. Results: Rates of optimal cytoreduction, severe postoperative morbidity and early oncological failure were 84·4, 25·7 and 29·0 per cent respectively. The median annual centre volume was 17 (range 6–66) peritoneal malignancies. Only eight of the 33 centres and six of 47 surgeons achieved proficiency after a median of 100 (range 78–284) and 96 (86–284) procedures respectively. The most important institutional factor affecting surgical performance was centre volume. Conclusion: The learning curve is extremely long, so centralization and/or networking of centres is necessary to assure quality of services. One centre for every 10–15 million inhabitants would be ideal. Abstract : One centre for every 10–15 million inhabitants ideal